Excellent Electrocatalytic Activity of Binuclear Phthalocyanines in the Electrolyte of Lithium/Thionyl Chloride Battery. Issue 8 (13th May 2016) - Liu, Zhijiao; Gao, Ruimin; Jiang, Qinqin; Zhang, Ronglan; Zhao, Jianshe; Wang, Junlong
Abstract : Binuclear nitro-phthalocyanines (M2 (PcTN)2 O) were synthesized and reduced to binuclear amino-phthalocyanines (M2 (PcTA)2 O) as high-efficiency catalysts to promote the electrochemical properties of lithium/thionyl chloride (Li/SOCl2 ) battery. The catalytic performances of M2 (PcTN)2 O and M2 (PcTA)2 O were evaluated by adding a small amount of catalysts into the electrolyte. Elemental analysis, Fourier transform infrared (FTIR), ultraviolet-visible (UV-vis), Thermal technique (TGA) and scanning electron microscope (SEM) were employed to characterize the final products. The discharge time of the battery catalyzed by M2 (PcTN)2 O and M2 (PcTA)2 O was lengthened by 181∼510 s and 198∼564 s, respectively. The results reveal that battery capacities had been improved approximately 16.74∼47.91% and energy increased by 14.95∼44.80% compared with the bare batteries, which should be attributed to the electronic configurations of the metal ions, the phthalocyanine rings and the synergistic effect. In addition, according to the cyclic voltammetric analysis, catalytic mechanism of the synthesized binuclear phthalocyanines in the battery was speculated.